Cost-effectiveness analysis of radiofrequency renal denervation for uncontrolled hypertension in Spain - Oriol Rodríguez-Leor; Khoa N. Cao; Fernando Jaén-Águila; Tamara García-Camarero; Carlos Mansilla-Morales; Michael Kolovetsios; María Álvarez-Orozco; José Antonio García-Donaire; Jan B. Pietzsch (REC: Interventional Cardiology (English Ed.))
ABSTRACT Introduction and objectives: Radiofrequency (RF) renal denervation (RDN) has been shown to be a safe and effective treatment option for patients with uncontrolled hypertension. This analysis sought to explore the cost-effectiveness of this therapy in Spain. Methods: A decision-analytic Markov model projected clinical events, quality-adjusted life years (QALY) and costs over the patients’ lifetime. Treatment effectiveness in the base case analysis was informed by the change in office systolic blood pressure observed in the full cohort of the SPYRAL HTN-ON MED trial (–4.9 mmHg vs sham control). Alternate scenarios were calculated for effect sizes reported in the HTN-ON MED subcohort of patients on 3 antihypertensive medications treated outside the United States, the HTN-OFF MED trial, and the Global SYMPLICITY Registry high-risk and very high-risk cohorts. The analysis was conducted from the Spanish National Health System perspective and a willingness-to-pay a threshold of €25 000 per QALY gained was considered. Results: RF RDN therapy resulted in clinical event reductions (10-year relative risk 0.80 for stroke, 0.88 for myocardial infarction, and 0.72 for heart failure) and a lifetime gain of 0.35 (13.99 vs 13.63) QALYs. Incremental lifetime costs were €5335 (€26 381 vs €21 045), resulting in an incremental cost-effectiveness ratio of €15 057 per QALY gained. Cost-effectiveness was further improved among all the other clinical evidence scenarios. Conclusions: The results of this study suggest that RF RDN can provide a cost-effective alternative in the treatment of uncontrolled hypertension in Spain.